ANALISIS MAJAS PADA CERITA PENDEK “LOVE IN APPLE” KARYA NURILLAIYAH - Mega Cahyani; Wikanengsih Wikanengsih; Enung Nurhayati (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This research was conducted because it was found in the short story "Love In Apple" by Nurillaiyah which has many figures of speech in each written story line. The researcher limits the analysis of this short story to the figure of speech contained in the short story. Through this research, the author has a research objective, namely to examine what figures are contained in the short story text "Love In Apple" by Nurillaiyah so that readers are able to gain knowledge about the elements of figure of speech that can be used as lessons and experiences in life to be used as examples in everyday life. For this study the authors used a research method with statistical studies to analyze the figure of speech contained in the short story, this research was conducted by reading the short story first, then analyzing and marking the text included in figure of speech, then from the data that was analyzed the researcher found There are various types of figure of speech contained in Nurillaiyah's short story “Love In Apple”, namely the comparative figure of speech, including association, hyperbole, simile and metaphor, then the affirmation figure, namely pleonasm. The conclusion is that the short story "Love In Apple" by Nurillaiyah is suitable for reading even by adolescents, adults and the general public.